Marshall’s The Migration: The Aesthetics of Nonhuman Metamorphosis, Environmental entanglements and the Posthuman Wound. - Chapman, Ana María (My University, 2024)
Helen Marshall’s novel, The Migration portrays a near-future apocalyptic world afflicted with global climate change and biological transformations. Floods and an unnerving immunological disease threaten human kind as an individuating biological force. In a non-binary nature-human portrayal, the narrative allows new ways of understanding human “matter” as fluid and embedded in its environment. Barad’s theories on new materialism provide insights into postanthropocentric “more-than-human relationality”observable in the narrative. Moreover, the example of human “matter” being transformed by disease, brings about mental and body trauma to humanity. New organic changes pose questions on relational, transformational and unstable materialism to the human body. With this new metamorphosis of the corporeal, ethical encounters, ontological and epistemological debates (i.e. Barad’s ethico-onto-epistem-ology) are present and hence, human bodies become ground for critical analysis of the anthropocentric, questioning traditional scientific approaches to the body. Drawing on ecocriticism and on authors such as Derrida, Braidotti and Barad, the novel will be examined in its inclusion of human trauma that goes beyond the biological anguish of not being central to evolution (Peters 2020) and in the trauma of human’s core sense of self where nostalgia of recovery has no place. I propose that the wound caused on the novel’s characters becomes the site for dissembling the anthropocentric paradigm and consequently points towards a nonhuman egalitarian system where nature’s embedded and relational modes transcend the boundaries of its biological individual expressions.
Keywords: Literatura inglesa; New materialism; Posthumanism; Contemporary literature